2012
DOI: 10.1007/s10853-012-6345-y
|View full text |Cite
|
Sign up to set email alerts
|

α′-Martensite formation in deep-drawn Mn-based TWIP steel

Abstract: To understand the formation of a 0 -martensite in high stacking fault energy twinning-induced plasticity steel deformed in the deep drawing mode, the existing phases were investigated using magnetic and transmission electron microscopy (TEM). Small fractions of a'-martensite were quantitatively determined by magnetization saturation experiments and further observed by TEM. TEM revealed the formation of a 0 -martensite at shear band and twin intersections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…, however van Tol et al [32] have observed small fractions of α (≤ 1.2%) in a TWIP steel during deep drawing; the stacking fault energy calculated for this steel was 50 mJ m −2 . As the fraction of α is very low for this steel with high-stacking fault energy, it will be assumed that is the main precursor for the γ → α transformation under uniaxial loading [3].…”
Section: α Martensite Formationmentioning
confidence: 72%
“…, however van Tol et al [32] have observed small fractions of α (≤ 1.2%) in a TWIP steel during deep drawing; the stacking fault energy calculated for this steel was 50 mJ m −2 . As the fraction of α is very low for this steel with high-stacking fault energy, it will be assumed that is the main precursor for the γ → α transformation under uniaxial loading [3].…”
Section: α Martensite Formationmentioning
confidence: 72%
“…Depending on the stacking fault energy, α′ martensite forms directly from austenite or via the hexagonal ϵ‐martensite. It is also recently reported that the formation of strain‐induced α′ martensite does not necessarily require the intermediate formation of ϵ‐martensite …”
Section: Resultsmentioning
confidence: 95%
“…It is also recently reported that the formation of strain-induced a 0 martensite does not necessarily require the intermediate formation of e-martensite. [33] Figure 4c reveals austenite grain, embedded with Moiré fringes with an average spacing (<10 nm). The TEM image also indicates that the fringes are stepped or curved due to the presence of high-density dislocations.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of α'martensite may occur by the nucleation and coalescence of new α'-martensite nuclei repeatedly [35]. Despite the general idea that α'-martensite may form just in low SFE steels [9], however van Tol et al [37] reported small fractions of α'-martensite (<1.2%) in a TWIP steel during deep drawing by SFE of 50 mJ/m 2 . It can be expected that ɛ-martensite is the main precursor for the γ→α' transformation in this case [2].…”
Section: Deformation Mechanismsmentioning
confidence: 99%